Menstrual pattern of severe intrauterine adhesion following hysteroscopy adhesiolysis (Bangladesh Journal of Medical Science, 2020)
Objective: The purpose of this study was to evaluate the menstrual and uterine shape in patients diagnosed with severe intrauterine adhesion (IUA) on hysteroscopy and to assess the outcome following hysteroscopic adhesiolysis.Materials and methods: It is a retrospective study of patients with severe intrauterine adhesion who attended with complain of infertility, abortion , and repeated dilatation and curettage to our institution from January 2017 and December 2017. Post hysteroscopic adhesiolysis the inserted of urinary balloon catheter and intrauterine device (IUD). The sodium hyaluronate gel was administered inside the uterus and oral cyclical hormonal treatment was initiated after the surgery to all patients to prevent reformationof adhesion, and promote endometrial regeneration respectively. The outcome of menstrual pattern and uterine shape were retrospectively analyzed. Data analyzed was performed with SPSS for Windows, version 20.0). Statistically signiﬁcant level was set at p